Lung and gut microbiomes in pulmonary aspergillosis: Exploring adjunctive therapies to combat the disease - Cai, Liuyang; Gao, Peigen; Wang, Zeyu; Dai, Chenyang; Ning, Ye; Ilkit, Macit; Xue, Xiaochun; Xiao, Jinzhou; Chen, Chang (Frontiers in Immunology, 2022)
Species within the Aspergillus spp. cause a wide range of infections in humans, including invasive pulmonary aspergillosis, chronic pulmonary aspergillosis, and allergic bronchopulmonary aspergillosis, and are associated with high mortality rates. The incidence of pulmonary aspergillosis (PA) is on the rise, and the emergence of triazole-resistant Aspergillus spp. isolates, especially Aspergillus fumigatus, limits the efficacy of mold-active triazoles. Therefore, host-directed and novel adjunctive therapies are required to more effectively combat PA. In this review, we focus on PA from a microbiome perspective. We provide a general overview of the effects of the lung and gut microbiomes on the growth of Aspergillus spp. and host immunity. We highlight the potential of the microbiome as a therapeutic target for PA.